Pengembangan Lembar Kerja Peserta Didik Berbasis Masalah pada Pembelajaran Pemograman Mikroprosesor dan Mikrokontroler - Selfi Harowanti; Muldi Yuhendri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This research is motivated by several things, namely the limitations of supporting books for student books, students still have difficulty mastering the learning material well. This study aims to develop a valid and practical student worksheet for Microprocessor and Microcontroller Programming in SMKN 1 Koto XI Tarusan. The research method uses the type of research R & D (Research & Development) with the 4D development model (Define, Design, Develop and Disseminate). Data were collected using the LKPD validation and practicality instrument sheet, the LKPD validity questionnaire and the LKPD practicality questionnaire. The subjects of this study were problem-based microcontroller and microprocessor programming LKPD, with research respondents as class XI TAV 2 students and PMM subject teachers at SMKN 1 Koto XI Tarusan. The questionnaire used in the study was in the form of a Likert scale with a score of 1 to 5. The results of the research on the development of problem-based Student Worksheets on the distribution of the mediation validation questionnaire obtained the average percentage results on valid criteria, the material validation questionnaire distribution obtained the average percentage result On the valid criteria, the teacher practicality questionnaire got the average percentage result on the very practical criteria and the students' practicality questionnaire got the average percentage results on the practical criteria. The results of this study indicate that the development of problem-based Student Worksheets made for Microprocessor and Microcontroller Programming subjects has been criticized as valid and practical.